Pengaruh Perkembangan Teknologi dan Kinerja Pendidikan Terhadap Pengangguran di Indonesia - Hadi Priyono, Teguh; Gianavasya, Shelsa; Hanim, Anifatul; Yunitasari, Duwi; Wibisono, Sunlip; Jumiati, Aisah (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
Digitalization and rapid technological developments can affect a country's economic performance, whether it has a positive impact on economic growth or can even cause other problems such as unemployment. This study aims to determine the effect of technological developments, educational performance, and economic growth on the open unemployment rate in Indonesia. The research was conducted using explanatory research methods and quantitative approaches, as well as using panel data regression analysis methods. The data retrieval is done by using secondary data taken from the Central Statistics Agency website which consists of cross section and time series data by 34 provinces in Indonesia in 2015 – 2020. The test is carried out with the stages of estimating multiple linear regression models and produces the best model, namely Random Effect Model, then Statistical Test, and through the final stage of classical regression assumption test. The results of the study concluded that there was a negative and significant relationship on all independent variables, namely IP-TIK, APK-SMA and economic growth (control) on the dependent variable, namely the open unemployment rate in Indonesia. And there is a role of depressing and interfering variables by the control variable of economic growth.